Analisis Kemampuan Numerasi Siswa Berdasarkan Hasil Asesmen Kompetensi Minimum di Sd Inpres Maponu - mona yulia123; herlina; yusdin garamusu; surahman (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
This study aims to assess students' numeracy skills based on the results of the Minimum Competency Assessment. This research is a descriptive qualitative study. The study was conducted at SD Inpres Maponu, Sarjo Sub-district, Pasangkayu District, West Sulawesi. Data collection techniques included observation, numeracy tests, interviews, and documentation. The data analysis was conducted using the Miles and Huberman interactive model. The findings of the study revealed that two students demonstrated low numeracy skills, with an average score of 19.01%, two students exhibited moderate numeracy skills, with an average score of 34.37%, and two students displayed high numeracy skills, with an average score of 46.61%. The overall average score for the Minimum Numeracy Competency Assessment at SD Inpres Maponu was 64%, indicating that the students' numeracy skills are classified within the moderate category. Each student, regardless of their score level (low, moderate, or high), faced individual challenges during the assessment process.